Pengelolaan Stres dan Ketahanan Keluarga: Studi Pada Caregiver Skizofrenia - Iyulen Pebry Zuanny (Pusat Studi Wanita UIN Ar-Raniry, 2025)
Having a family member with schizophrenia is not easy. Caregivers will naturally experience physical exhaustion and may even fall ill. Psychologically, they may experience burnout and stress. Behaviorally, caregivers may express emotions such as irritation, anger, sadness, apathy, and even aggression. Socially, caregivers may feel ashamed, isolated, and this can affect the functioning or resilience of the family. Ideally, a caregiver should be able to adapt and grow in the face of crisis or severe pressure while accompanying a schizophrenia patient, maintaining a healthy mind and body and achieving good family resilience. The results of the assessment using the Subjective Units of Distress Scale (SUD's) (1-10) on six caregivers who regularly visit health care facilities showed stress levels in the moderate to high categories. This was reinforced by the results of interviews with several caregivers and health workers who stated that many caregivers experience stress and low resilience within the family. One effort that can be made to deal with stress and low family functioning is to obtain psychological intervention for stress management. This study aims to examine the effect of stress management intervention on caregivers of schizophrenia patients. This study uses a quasi-experimental approach with a one-group pretest-posttest design consisting of 4 sessions. The sampling technique in this study uses purposive sampling. The results of the study show that there is a change in SUD's scores among caregivers, which directly affects family resilience.